The role of canonical and non-canonical inflammasomes in a model of oxidative stress-induced retinal degeneration - Silke, Eoin (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2024)
Retinal degenerative diseases like age-related macular degeneration (AMD) are a leading cause of visual impairment. Oxidative stress is known to be important in the pathogenesis of AMD, and oxidative-stress induced retinal degeneration can be studied using various models. The sodium iodate mouse is a widely used animal model of retinal degeneration, but its pathobiology is not well understood. Activation of innate immune pathways is suspected to play an important role in retinal degeneration secondary to oxidative stress. We investigated both canonical and non-canonical inflammasomes in sodium iodate-induced retinal degeneration in two types of genetic knockout mice (Pycard-/- and Casp11-/-). Pycard-/- mice are deficient in ASC protein which prevents the majority of canonical inflammasomes from forming, whereas deficiency in caspase-11 prevents non-canonical inflammasome activation. Using in vivo optical coherence tomography measurements, histological analysis, and TUNEL staining we observed that in Pycard-/- mice, loss of canonical inflammasome formation did not appear to affect oxidative stress-induced retinal damage. However, knocking out caspase- 11 and thus inhibiting non-canonical inflammasome pathways may limit oxidative stress- induced retinal degeneration.
APPROVED